Pengaruh Motivasi, Kompetensi dan Lingkungan Kerja Terhadap Kinerja Karyawan PT. Wijaya Elnusa Semarang - Rr. Mega Ayu Pratiwi; Widiartanto Widiartanto (Jurnal Ilmu Administrasi Bisnis, 2017)
Every company needs the resources that have important influence to achieve success. Success in achieving the organization's goals came from the behavior of its own employees therefore the employees that make up the structure of the organization and take advantage of technology. Performance of the employee is influenced by several factors such as motivation, competence and Working Environment. Poor performance of the employee caused by low motivation, lack of competence and a poor working environment at PT. Wijaya Elnusa Semarang.This research uses explanatory type approach, against 50 respondents with sampling purposive technique. Data collection techniques in this study using the technique of collecting data through questionnaires and interviews. The analysis technique used is quantitative. Quantitative analysis using validity test, reliability test, cross tabulation, correlation coefficient, coefficient of determination, simple and multiple regression analysis, as well as the significance test (t test and F test) with the help of SPSS version 16.0 for Windows.The results of statistical analysis known partial influence between motivation on performance of the employee by 63.3%. Then competence to performance of the employee by -2.1%. while for the working environment on the performance of the employee by 18,4%. Simultaneous influence of the influence of motivation, competence and working environment on the performance of the employee is 80.5%, while 19.5% are influenced by other factors.Recommendations for improving the performance of employees to the company to increase its attention to the work motivation, competence and working environment which in turn will ultimately increase performance of the employee.